The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acs.analchem.2c02081
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic-Derived Detection of Protein-Facilitated Copper Flux Across Lipid Membranes

Abstract: Measurement of protein-facilitated copper flux across biological membranes is a considerable challenge. Here, we demonstrate a straightforward microfluidic-derived approach for visualization and measurement of membranous Cu flux. Giant unilamellar vesicles, reconstituted with the membrane protein of interest, are prepared, surface-immobilized, and assessed using a novel quencher–sensor reporter system for detection of copper. With the aid of a syringe pump, the external buffer is exchanged, enabling consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“… 298 On the other hand, molecular robots with sensors and computers may be able to fill this gap. Previous studies have reported that GUVs with nanopores are useful for the detection of K + , 56 Cu 2+ , 299 and Cl − . 300 Recently, a unique strategy using GUVs with a DNA nanopore and circuit offered by Peng et al suggested switchable detection of Sr 2+ (ref.…”
Section: Applications Of Molecular Robotsmentioning
confidence: 99%
“… 298 On the other hand, molecular robots with sensors and computers may be able to fill this gap. Previous studies have reported that GUVs with nanopores are useful for the detection of K + , 56 Cu 2+ , 299 and Cl − . 300 Recently, a unique strategy using GUVs with a DNA nanopore and circuit offered by Peng et al suggested switchable detection of Sr 2+ (ref.…”
Section: Applications Of Molecular Robotsmentioning
confidence: 99%